Awareness, Perception, and Utilization of Skin Lightening Agents Among Females of Asmara, Eritrea: A Cross-Sectional Study - Tesfamariam S; Bahta M; Weldemariam DG; Tesfamariam EH; Yemane H; Bahta I; Russom M (Dove Medical Press, 2023)
Sirak Tesfamariam,1 Merhawi Bahta,1 Dawit G Weldemariam,2 Eyasu H Tesfamariam,3 Hermella Yemane,1 Iyassu Bahta,1 Mulugeta Russom1,4,5 1National Medicines and Food Administration, Ministry of Health, Asmara, Eritrea; 2Pharmacy, Hazhaz Zonal Referral Hospital, Asmara, Eritrea; 3Department of Statistics, Eritrean Institute of Technology, Mai-nefhi, Eritrea; 4Department of Medical Informatics, Erasmus Medical Center, Rotterdam, Netherlands; 5European Programme for Pharmacovigilance and Pharmacoepidemiology, University of Bordeaux, Bordeaux, FranceCorrespondence: Merhawi Bahta, Tel +2917294279, Email meramcp19@gmail.comBackground: The use of skin lightening agents (SLAs) is common among African females with black skin color. Although they usually contain harmful ingredients and can cause complications, their use remains to be a common practice. This study was conducted to assess the awareness, perception, and utilization of SLAs among females residing in Asmara, Eritrea.Methods: A cross-sectional analytical study using a quantitative approach was conducted in representative samples of all beauty salons available in Asmara from May to July, 2021. The study participants were selected using two-stage stratified cluster sampling and data were collected through a face-to-face interview using a structured questionnaire. Descriptive analysis and logistic regression, at bivariate and multivariate level, were performed.Results: The study enrolled 721 females and 684 completed the study. The majority of the respondents had the perception that SLAs can make someone light colored (84.4%), look beautiful (67.8%), trendy and fashionable (55.0%), and white skin is more attractive than dark skin (58.8%). About two-thirds (64.2%) reported they had previously used SLAs, mainly influenced by friends (60.5%). Approximately 46% were current users, while 53.6% stopped it mainly due to adverse effects, fear of adverse effects and ineffectiveness. A total of 150 products including natural ingredients were mentioned being used to lighten the skin, and Aneeza, Natural face, and Betamethasone containing brands were among the top used products. The occurrence of at least one adverse effect due to the use of SLAs was 43.7%, while 66.5% were satisfied with the use of SLAs. Additionally, employment status and perception of SLAs were found to be determinants of being a current user.Conclusion: Utilization of SLAs, including products containing harmful or medicinal ingredients, was prevalent among the females of Asmara city. Thus, coordinated regulatory interventions are recommended to tackle unsafe practices and raise public awareness to promote the safe use of cosmetics.Keywords: skin whitening, cosmetics, beauty salon, face-to-face interview